2017
DOI: 10.4103/0366-6999.211896
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Survival Analysis of Anatomic and Prognostic Stage Group Based on the American Joint Committee on Cancer 8th Edition Cancer Staging Manual in Luminal B Human Epidermal Growth Factor Receptor 2-negative Breast Cancer

Abstract: Background:Current understanding of tumor biology suggests that breast cancer is a group of diseases with different intrinsic molecular subtypes. Anatomic staging system alone is insufficient to provide future outcome information. The American Joint Committee on Cancer (AJCC) expert panel updated the 8th edition of the staging manual with prognostic stage groups by incorporating biomarkers into the anatomic stage groups. In this study, we retrospectively analyzed the data from our center in China using the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
(20 reference statements)
2
15
0
Order By: Relevance
“…The results obtained confirm that integration of tumour load (size and presence of node involvement) with tumour type (grade and prognostic factors) leads to an increased number of patients classified as stage I, as previously reported. 16,17 Furthermore, in line with other studies, 18,19 we found that stage I according to PS clearly identifies a group of patients with a more favourable outcome, distinguishing them from other patients with lesions classified as stage II or III and providing more accurate prognostic information compared with AS.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained confirm that integration of tumour load (size and presence of node involvement) with tumour type (grade and prognostic factors) leads to an increased number of patients classified as stage I, as previously reported. 16,17 Furthermore, in line with other studies, 18,19 we found that stage I according to PS clearly identifies a group of patients with a more favourable outcome, distinguishing them from other patients with lesions classified as stage II or III and providing more accurate prognostic information compared with AS.…”
Section: Discussionsupporting
confidence: 90%
“…The evaluation of these cancer biomarkers in liquid biopsy has the advantage of providing a real-time picture of primary and metastatic tumors at different time points, giving information about tumor and tumor burden and early evidence of drug resistance and tumor recurrence (Di Meo et al, 2017). Moreover, liquid biopsy analysis allows defining of the DNA molecular profile of cancer patients, whose inclusion in the tumor, node, and metastasis staging system may help to develop more highly personalized therapies and decrease risks of inappropriate treatments (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study published by Wang M et al 4 found that the prognostic stage provided accurate prognostic information for locally advanced breast cancer compared with anatomic TNM stage. In China, Liu YH et al [5][6][7] published a series of articles about the prognostic value of the new staging system in luminal A, luminal B, HER2-negative, HER2-enriched breast cancer patients, demonstrating that the prognostic stages refines the anatomic stages and will lead to a more personalized guidance to the selection of therapy. More additional retrospective studies have also confirmed the improved accuracy of the new staging system and its increasing relevance under the current medical strategies.…”
Section: Introductionmentioning
confidence: 99%